1985
DOI: 10.1007/bf02266951
|View full text |Cite
|
Sign up to set email alerts
|

Regulators of cell division in plant tissues. XXX. Cytokinin metabolism in relation to radish cotyledon expansion and senescence

Abstract: Abstract. Kinetic studies of formation of glucosides of 6-benzylaminopurine (BAP) in excised radish cotyledons indicated that the 3-, 7-, and 9-glucosides (N-glucosides) were each formed directly from BAP. The 7-and 9-glucosides of BAP and the 7-glucoside of zeatin exhibited great stability in the cotyledons, but the 3-glucoside was converted to free BAP and to the 7-and 9-glucosides of BAP. When 3H-labeled zeatin was supplied to developed cotyledons, at high concentrations (100 I~M), 7-glucosylzeatin was the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…This is in accord with previous studies. Indeed it was found that a 90% reduction in 3H-labeled cytokinin uptake by radish cotyledons did not appreciably change the percentage of radioactivity present as N-glucosides (Letham and Gollnow 1985). Hence, the inhibitorinduced reductions in cytokinin uptake do not affect the validity of the data presented in Tables 1 and 2.…”
Section: Inhibition By Methylxanthines and Papaverinementioning
confidence: 92%
See 2 more Smart Citations
“…This is in accord with previous studies. Indeed it was found that a 90% reduction in 3H-labeled cytokinin uptake by radish cotyledons did not appreciably change the percentage of radioactivity present as N-glucosides (Letham and Gollnow 1985). Hence, the inhibitorinduced reductions in cytokinin uptake do not affect the validity of the data presented in Tables 1 and 2.…”
Section: Inhibition By Methylxanthines and Papaverinementioning
confidence: 92%
“…The presence of (OG)Z was confirmed by 13-glucosidase hydrolysis and rechromatography. When the cotyledon extracts were subjected to chromatography using a bilayer 2D TLC system (Letham and Gollnow 1985), the percentages of radioactivity found for the various metabolites were similar to those determined by the procedure outlined above. Eluates of the 2D TLC Z and [9R]Z spots, derived from extracts of cotyledons supplied with [3H][9R]Z in the presence of some inhibitors, were rechromatographed using TLC systems (Parker et al 1978) which separate Z from dihydrozeatin (DZ) and [9R]Z from dihydrozeatin riboside [9R]DZ.…”
Section: [9r]z [7g]z Plus O-glucosyl Zeatin [(Og)z] Adenine (Ade) mentioning
confidence: 99%
See 1 more Smart Citation
“…For reversed phase TLC, layers spread with Merck silica gel 60 GF254 were impregnated with dimethylpolysiloxane-5X (Letham and Gollnow 1985) and are termed DMPS layers henceforth . The following solvents were used (proportions are by volume) : A, 1-butanol-water-14 N ammonia (6 :2 :1, upper phase) ; B, methanol-water (1 :1); C, chloroform-methanol (9 :1); D, methanol-water (2 :3) ; E, propyl acetate-acetic acid-water (20 :9 :5); F, 1-butanol saturated with water .…”
Section: Chromatographic Methodsmentioning
confidence: 99%
“…Cytokinin bases (Z, DZ, and iP) and Z-9-glucoside were measured directly, but the O-glucosides were first hydrolyzed to bases with ␤-glucosidase (Yong et al 2000). Z-7-glucoside was converted to Z by periodate oxidation and cleavage with freshly distilled cyclohexyl-amine (Letham and Gollnow 1985) before immunoassay.…”
Section: Quantification Of Cytokininsmentioning
confidence: 99%